Variant phrase units in the Belarusian paremiological collections of the 19th century - Koshkina, Natallia Ja. (Journal of the Belarusian State University. Philology, 2023)
In the article, the variable units in the phraseological system of the Belarusian literary language of the 19th century are analysed. At the same time, the material from collections of proverbs by I. I. Nosovich, E. R. Romanov, P. M. Shpilevsky, and E. A. Lyatsky is used. The variant units recorded in each collection and the variants from different publications are investigated. Variant types are singled out, and illustrative material is given. Conclusions are drawn about the nature of phraseological variability, which serves as an indicator of a certain level of development of the language system at that time.
Keywords: variance; phraseology; paremia; phraseological unit; variant series; variant types; phraseological norm